Handbook of non-motor symptoms in Parkinson's Disease - Chaudhuri, K Ray (Springer, 2011)
Handbook of Non-Motor Symptoms in Parkinson's Disease is designed to provide practical tips and emphasize key priorities for treatment of non-motor aspects of the disorder. The quick-reference handbook format, with key points highlighted by the use of figures and tables, will provide the reader with high-value practical information.